O conceito de compreensão na histórica de Johann Gustav Droysen - Cremonezi, André Roberto (2005)
This dissertation has the aim to analyse and reconstruct the concept of Investigative Comprehension forschendes Verstehen inside the Johann Gustav Droysen's Historik . Through the theoretical elements offered by the mentioned German historian of the 19th Century, he tries to examine the grounds presented as basis for the hermeneutic comprehension, as the centre of an undertaking that aspires to grant normative and methodological autonomy to the historical science. The mentioned analysis is fulfilled by a brief reconstruction of the German historicist context in the second half of the 19th Century, as well as by the presentation of the different constituent moments of the historical method formulated by Droysen, making explicit the inherent peculiarities in the compilation of the Historik . Among the obtained results lies the verification of a complex interlacement between a transcendental philosophy and an ontology of the history just in the basis of the Investigative Comprehension, as well as the universalisation that the above-mentioned notion attributes to the hermeneutic problem of the comprehension, prior to the project of a Critique of the Historical Reason.